Monitoring two-stage processes with binomial data using generalized linear model-based control charts. Issue 3 (2nd July 2016) - Amiri, Amirhossein; Yeh, Arthur B.; Asgari, Ali
Abstract: In this study, we propose a control chart for monitoring two-stage processes whose quality characteristic to be monitored in the second stage follows a binomial distribution. The proposed control chart is based on the deviance residual in which essentially the generalized log-likelihood ratio statistic is obtained from the generalized linear model. To establish the relationship between the first- and second-stage quality characteristics, we propose using a new link function in a generalized linear model framework. The performance of the proposed control chart with the new link function is compared with that under the traditional logit link function in terms of the average run length criterion. In addition, the performance of the proposed control chart is compared with the chart designed based on the original residuals under the new link function as well as the traditional np -chart applied for monitoring the binomial quality characteristic in the second stage.